Risk of inflammatory bowel disease appears to vary across different frequency, amount, and subtype of alcoholic beverages - Liu, Bi-Xia; Yang, Jing; Zeng, Chunyan; Dai, Xi-Jian; Chen, Youxiang (Frontiers in Nutrition, 2022)
Abstract Objective: Inflammatory bowel disease (IBD) and alcohol use has become a significant and growing public health concern. Alcohol use has been reported to be the most-avoided diet item among IBD patients. However, knowledge regarding the impact of different classes of alcoholic beverages on the management of IBD are limited. The aim of our study is to evaluate the association of different frequency, amount, and subtype of alcoholic beverages with IBD risk. Methods: UK Biobank comprised 7095 subjects with IBD and 495410 subjects without. Multivariate Logistic regression, stratifying analysis and interaction term were used to estimate the odds ratios (ORs) and 95% confidence intervals (95% CIs) of IBD. A generalized additive model was used to evaluate the linearity associations of the amount of alcohol consumption or that of alcoholic beverages with IBD risk. Results: Compared with non-drinkers, the IBD risk was 12%-16% lower in red wine consumers (1-2 glasses/week, OR [95%CI], 0.88 [0.80, 0.97]; 3-4 glasses/week, 0.84 [0.76, 0.93]; ≥5 glasses/week, 0.86 [0.78, 0.95]), whereas 12% higher in white wine and champagne consumers (1-2 glasses/week, 1.12 [1.03, 1.22]). Stratifying analysis showed low frequency red wine consumers were associated with a lower IBD risk (0.85 [0.74, 0.97]), whereas spirits was associated with a higher risk (1.28 [1.03, 1.59]). High doge red wine consumers were associated with a lower IBD risk (above guidelines, 0.80 [0.67, 0.97]; double above, 0.83 [0.71, 0.97]), whereas high doge white wine and champagne (1.32 [1.09, 1.61]) and beer and cider (1.26 [1.02, 1.54]) consumers were associated with a higher IBD risk. White wine and champagne showed a significant interaction effect with high doge alcohol consumption (1.27 [1.03-1.58], p = 0.029). The dose-response association showed an increased IBD risk with a greater number of alcohol consumption for white wine and champagne, beer and cider and total amount of alcohol intake. However, red wine is at low risk across the whole dose cycle. Conclusions: The IBD risk appears to vary across different frequency, amount, and subtype of alcoholic beverages. Overall, alcohol intake is not recommended and the safe level of drinking appears to be none.